Tinjauan Yuridis Terhadap Anggota Koperasi Dalam Hal wanprestasi Atas Pelaksanaan Perjanjian Kredit Pada Koperasi Unit Desa - Jihan Fadila; Zaini Munawir; Marsella Marsella (JUNCTO: Jurnal Ilmiah Hukum, 2022)
In the process of granting credit, it is often the case that the creditor is detrimental when the debtor defaults, so we need a rule contained in a credit agreement that aims to provide certainty for the related parties. The research objectives to be achieved in this study are to determine the procedure for implementing credit agreements, to determine dispute resolution when a member of a cooperative defaults in a credit agreement, to find out the legal consequences if a member of a cooperative defaults in a credit agreement. The research method used is Library Research and Field Research. Juridical research type normative. The conclusion obtained is the procedure contained in KUD "Harta" Langkat to perform a credit agreement by way of : submitting an application, providing information on the object of the guarantee, observing the object of the collateral, and approving the object of the guarantee. Settlement of default disputes in credit arrangements at KUD "Harta" Langkat takes several ways, namely litigation and non-litigation, but in accordance with the cooperative principle, it must first be resolved by agreement, if not resolved, it will be resolved through legal channels. Legal consequences arising from default in credit arrangements at KUD "Harta" Langkat by giving a warning letter and if the obligations are not fulfilled then the status can be abolished.